Analisis Kesenjangan Sosial di Sekolah: Perspektif Sosiologi Pendidikan Islam (Studi Kasus di SDN Bhayangkara Yogyakarta) - Amanullah, Wahyu Anis; Wantini, Wantini (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The sociology of education has a crucial role in developing a more optimal and efficient education system. One of the major bottlenecks in the sociology of education is the educational gap. The sociology of education is a sociological analysis used to solve the main issues faced in the realm of education. The purpose of this study is to analyze social inequality in schools from the perspective of Islamic education sociology. The research approach uses qualitative research. This research was conducted at SDN Bhayangkara. The subject of this research is the teacher. Data collection techniques using observation, interviews, and documentation. Data analysis used data reduction, data display, and data conclusion verification. The results of the research can be concluded that social inequality also occurs not only in the community but in the educational environment this often occurs. SDN Bhayangkara is a public school located in the middle of the urban city of Yogyakarta. Students with various kinds of social, and economic status, parenting patterns, and different environments have resulted in social inequality in the school environment such as at SDN Bhayangkara. The application of the sociology of Islamic Education with counseling guidance, there is moral material, there is an example, there is punishment and religious activities. Through the application of the sociology of Islamic education, it is hoped that it can prevent social inequalities that occur in schools.